2010
DOI: 10.1039/c0dt00908c
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent materials of annealed Eu3+-exchanged zeolite L crystals

Abstract: In this work, we report the luminescence behavior of Eu(3+)-exchanged zeolite L microcrystals annealed at different temperatures. SEM and XRD techniques were employed to characterize the samples. UV-vis absorption spectroscopy and luminescence spectroscopy were used to study the luminescence properties of the annealed materials. It is shown that Eu(3+)-exchanged zeolite L crystals are structurally stable at 800 °C, and that its structure is completely collapsed when annealed at 1100 °C. Calcination of Eu(3+)-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…As previously reported, a strong and broad emission band peaking at 400 nm can be obtained for Eu 3+ /ZL-H 2 O when the excitation wavelength was 320 nm; no sharp emission lines of 5 D 0 A 7 F J (J = 0-4) can be observed. 27 The excitation band has been assigned to the transition from the ground state of Eu 2+ (4f 7 ) to the 4f 6 5d 1 state, the intense emission band has been attributed to the typical transition, 4f 6 5d 1 A 4f 7 . 30 As is well known, Eu 2+ emissions from the UV part to the red part can be achieved depending on symmetry and crystal field strength around Eu 2+ .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…As previously reported, a strong and broad emission band peaking at 400 nm can be obtained for Eu 3+ /ZL-H 2 O when the excitation wavelength was 320 nm; no sharp emission lines of 5 D 0 A 7 F J (J = 0-4) can be observed. 27 The excitation band has been assigned to the transition from the ground state of Eu 2+ (4f 7 ) to the 4f 6 5d 1 state, the intense emission band has been attributed to the typical transition, 4f 6 5d 1 A 4f 7 . 30 As is well known, Eu 2+ emissions from the UV part to the red part can be achieved depending on symmetry and crystal field strength around Eu 2+ .…”
Section: Resultsmentioning
confidence: 96%
“…[24][25][26] We recently found that annealing of Eu 3+ -functionalized ZL (Eu 3+ /ZL) at 400 to 800 uC can produce a strong and bright violet-blue emission. 27 However, the real origin of the emission is still not clear although we proposed it might be due to the Eu 2+ centers resulting from the reduction of Eu 3+ located in the channels of ZL crystals during the annealing process. Our aim here is to identify the origin of the strong violet-blue emission and to study the preparation variables on the emitting colors of the obtained Eu 3+ /ZL luminescent materials.…”
Section: Introductionmentioning
confidence: 85%
“…[17][18][19][20][21][22][23] Up to now, the typical hosts used for Ln 3+ ions or lanthanide complexes are two types of synthetic zeolites, including faujasite-type zeolite (i.e. zeolite X and zeolite Y) 7,20 and zeolite L. 11,[23][24][25][26][27] In addition, there have been a few reports on Ln 3+ /zeolite A or ZSM-5-based hostguest materials. 22,[28][29][30][31][32][33][34] Zeolites X and Y with the cubic faujasite (FAU) framework structure (Fig.…”
Section: Huanrong LImentioning
confidence: 99%
“…40 Considering the merits of ZL crystals and encouraged by the promising results from Ln 3+ species in other zeolites, we have developed a series of host-guest materials based on ZL crystals and Ln 3+ species. 11,23,26,44 The advantages of ZL instead of other zeolites and silica are as follows: 1) the size of the ZL crystal can be synthetically tuned from 30 nm to 20 μm with different morphologies, ranging from discs to elongated cylinders, for use in different experiments, 2) the hexagonal structure of ZL crystals has strictly parallel one-dimensional channels, and 3) the facile functionalization of the surface of ZL with targeting groups.…”
Section: Huanrong LImentioning
confidence: 99%
See 1 more Smart Citation